Investigation of Toxoplasma gondii Seroprevalence in People Keeping Cats and Not Keeping Cats at Their Home in Sivas - İbrahim Özmen; Ahmet Duran Ataş (Türkiye Parazitoloji Dergisi, 2023)
Objective: Toxoplasma gondii (T. gondii) is an obligate intracellular protozoan and its definitive host is the Felidae family. Toxoplasmosis can be transmitted to humans in many ways. The purpose of the study was to investigate the anti-Toxoplasma IgM and anti-Toxoplasma IgG seropositivity with the ELISA method in people who have cats at home and do not have cats at home, and to reveal the possible relationship between toxoplasmosis and people who keep/contact cats for a long time for any reason at home.